A evolução do conceito de soberania e a análise de suas problemáticas interna e externa - Machado, Marcelo Forneiro (2009)
The evolution of sovereignty s concept through works of several philosophers, lawyers, historians, who occupied themselves with this subject and made many politics doctrines and State theories, has had a big disagreement since its systematization by Jean Bodin and even before him, rooted in the late medieval thought. The sovereignty s concept analises facing the modern situation unveil to us that some countries are more sovereign than others, as they can defend their beliefs its sovereignty either by weapons or by finances. Therefore, sovereignty is more for a relative value, which would be connected to a strong international political condition. If in the outer level the concept of sovereignty find itself menaced by its inner level, that is national, it is no longer safe with the huge development of constitutional theory. The classic concept of sovereignty must be reviewed, once it is in no sense the idea of a power which does not find anything above itself, in the face of the problems showed, without the disregard to the profusion of the theoretic developments about its concept, which must be re-evaluated under a new point of view, measuring and comparing the importance of its maintenance, looking to the future of political-juridical relationships among the various bodies of international law. This study has as a goal to pass by such discussions, having basis on the analyses of several philosophical schools which dealt with the subject, contributing with the restructuration of this old concept, once its disregard seems to us undesirable, as we will conclude at the end